Stream of consciousness : unity and continuity in conscious experience - Dainton, Barry, 1958- (International library of philosophy., 2000)
An in-depth investigation into the phenomenology of conscious experience - the nature of awareness; introspection; phenomenal space and time consciousness. A fascinating and probing study.